2011
DOI: 10.1007/978-3-642-24559-6_23
|View full text |Cite
|
Sign up to set email alerts
|

Architectural Verification of Control Systems Using CSP

Abstract: Abstract. Although validation of complex dynamic systems can be realised using checklists and simulations provided by tools such as Simulink, these techniques usually do not cover all system behaviours. Moreover, the control laws are rarely modelled together with the system architecture. This integration can reveal defects which are only detected in final stages of the development. This work presents two major contributions: a strategy to validate the integration of a proposed architecture with control laws, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The failure logic is essential for system safety assessment because it is used as basic input for building fault trees (Papadopoulos et al 2001;Jesus et al 2011;Gomes et al 2010). Furthermore, we still connect the strategy presented in Mota et al (2010) with the works reported in Jesus et al (2011) (functional analysis) and in Gomes et al (2010) and Papadopoulos et al (2001) (safety assessment) because our new algebra is at least a Boolean algebra.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The failure logic is essential for system safety assessment because it is used as basic input for building fault trees (Papadopoulos et al 2001;Jesus et al 2011;Gomes et al 2010). Furthermore, we still connect the strategy presented in Mota et al (2010) with the works reported in Jesus et al (2011) (functional analysis) and in Gomes et al (2010) and Papadopoulos et al (2001) (safety assessment) because our new algebra is at least a Boolean algebra.…”
Section: Resultsmentioning
confidence: 95%
“…To perform a formal verification in a Simulink system design model, the work reported in Jesus et al (2011) translates a Simulink model to the CSP M language. The resulting CSP M code is then used to check if it meets functional requirements also encoded in CSP M .…”
Section: Systems' Nominal Model and Faults Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conduct five sets of experiments 5 . The first set investigates the performance of refinement checking, by verifying the same model and assertion with different reduction techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from the decomposition, some data abstraction techniques can also be used to optimize the formal model. For example, Jesus et al [23] abstract any infinite domain in the system to allow checking the CSP models using FDR2.…”
Section: Related Workmentioning
confidence: 99%